The application of drug loading and drug release characteristics of two-dimensional nanocarriers for targeted treatment of leukemia - Yao, Yuan; Gao, Xiaoli; Zhou, Zaifu (Frontiers in Materials, 2023)
The development of bioinformatics technology has enabled nanomedicine to play a significant role in drug delivery systems. Its low toxicity, high efficiency, and controllable drug release advantages make it have good application effects. Moreover, common targeted therapeutic drug formulations have weak stability in malignant tumor leukemia, and their application effects are limited. Therefore, based on the characteristics of black phosphorus two-dimensional nanomedicine, experimental designs were conducted on its nanosheet preparation, polyethylene glycol modification, and anti-tumor drug loading. Experimental analysis was also conducted on the characterization ability, drug release, and targeted therapy of nanomedicine. The results show that polyethylene glycol (PEG) modified black phosphorus crystals (BP) nanoparticles can effectively improve their negative electricity, and have relatively stable photothermal properties. The release of doxorubicin hydrochloride (DOX) loaded nanoparticles was analyzed. It was found that the maximum drug release efficiency of BP-PEG-DOX was higher than that of BP-DOX at pH 5 and 7.5 (12.13% > 7.69%, 29.46% > 28.69%). The maximum drug release rates of BP-PEG-DOX-NIR reached 33.23% and 28.67% at temperatures of 35°C and 45°C, with differences of over 10% compared to the non laser group. Moreover, the nano drug loaded particles modified with PEG and treated with laser have a significant killing effect on cells, with a decrease in cell survival rate of over 15%. The two-dimensional nano drug carrier has high safety and effectiveness in drug delivery, and its targeted treatment effect on acute T lymphoblastic leukemia cells is obvious. Its drug release characteristics perform well in photothermal therapy, indicating that black phosphorus nano drugs can improve the biological safety and applicability of drugs in new tumor targeted therapy.